Research on the internal logic and solution of the “Channel Computing Resources from the East to the West” project - Nannan TONG; Dong CHEN; Huiying LI; Honglin ZHU (大数据)
The ＆quot;Channel Computing Resources from the East to the West＆quot; project is a major strategic project to build a balance of computing resources and on-demand scheduling in China's territorial space.Since the full launch of the Chinese＆quot;Channel Computing Resources from the East to the West＆quot; project construction, a series of problems have been exposed on many different fields, such as the supply side, demand side, energy side, technology side, and mechanism side.It is urgent to re-analyze and define the internal logic of the ＆quot;Channel Computing Resources from the East to the West＆quot;project from a theoretical level.The internal logic of ＆quot;Channel Computing Resources from the East to the West＆quot;, that is, the infrastructure of Chinese computing, was analyzed from different perspectives such as economic form, technological trend, technological competition, and cost-benefit.It also proposed to build a new type of infrastructure for the Chinese national computing network, called computing NET, and build a national computing NET construction path from the aspects of policy layout, network direct connection, technical support, and mechanism innovation.